2019
DOI: 10.1590/2177-6709.24.6.069-079.bbo
|View full text |Cite
|
Sign up to set email alerts
|

Immediate orthodontic load on dental implants: an option for adult treatment

Abstract: The demand for orthodontic treatment in adults has been increasing. However, these patients often require a multidisciplinary approach, due to the lack of posterior teeth, requiring additional anchorage. The skeletal anchorage by endosseous implants is an option, since they may be used later for prosthetic rehabilitation. The application of immediate load on these appliances for orthodontic movement may reduce the costs and total treatment time. This paper discusses the utilization of endosseous dental implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Dental implants are commonly and widely used for the oral rehabilitation of partially and completely edentulous patients [1], with other specific applications in maxillofacial prosthodontics and orthodontics [2]. Due to improved modern understanding of biomechanical aspects that primarily encompass the influence of load distribution on the biochemistry and physiology at the implant-bone interface [3], diagnostic and planning technologies [4], surgical techniques [5,6], and loading protocols [7,8], a high level of predictability can be achieved with dental implants to attain favorable treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Dental implants are commonly and widely used for the oral rehabilitation of partially and completely edentulous patients [1], with other specific applications in maxillofacial prosthodontics and orthodontics [2]. Due to improved modern understanding of biomechanical aspects that primarily encompass the influence of load distribution on the biochemistry and physiology at the implant-bone interface [3], diagnostic and planning technologies [4], surgical techniques [5,6], and loading protocols [7,8], a high level of predictability can be achieved with dental implants to attain favorable treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM), has been intensively used in several fields of dentistry for obtaining three-dimensional (3D) printed devices [1,2]. In orthodontics, printed surgical guides are used to aid miniimplant placement in the palatum.…”
Section: Introductionmentioning
confidence: 99%
“…In orthodontics, printed surgical guides are used to aid miniimplant placement in the palatum. Numerous studies have shown that the use of printed surgical guides for miniimplants have increased their placement precision in the anterior region of the palate, thus increasing the predictibility of the treatment with temporary anchorage devices (TADs) [1,3,[4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%